Data structures and algorithms for game developers. - Sherrod, Allen, ....- (Boston : Charles River, 2007)
"Data Structures and Algorithms for Game Developers" teaches the fundamentals of the data structures and algorithms used in game development. It provides programmers with a detailed reference to what data structures and algorithms are, and why they are so critical in game development. It teaches new game programmers, students, and aspiring game developers how to create data structures and write algorithms using C++. All key features of C++ are also covered, especially those related to game development. Additionally, a demo application is included in each chapter focusing on the data structure and/or algorithms presented in that chapter. The book covers many modern topics that game and graphics programmers must know to be successful, including geometry management techniques, and data structures and algorithms such as KD-Trees, Binary Space Partitioning Trees, Sphere Trees, etc. The code written in this book is not dependent on any specific hardware or operating system. Each chapter ends with questions, exercises, and challenges for the reader to complete in order to help them better understand and apply what they learn. Contents: 1. Introduction to data structures 2. Arrays 3. Recursion 4. Introduction to sorting 5. Link lists 6. Stacks and quees 7. Hash tables 8. Advanced sorting 9. Trees 10. Heaps 11. Graphs 12. Additional STL Algorithms 13. Scene Management 15. Conclusions
Keywords: Algoritmen; Computerspelen; Gegevensstructuren; Programmeren